2010
DOI: 10.1068/p6740
|View full text |Cite
|
Sign up to set email alerts
|

The Nose Tells it to the Eyes: Crossmodal Associations between Olfaction and Vision

Abstract: Crossmodal linkage between the olfactory and visual senses is still largely underexplored. In this study, we investigated crossmodal olfactory-visual associations by testing whether and how visual processing of objects is affected by the presence of olfactory cues. To this end, we explored the influence of prior learned associations between an odour (eg odour of orange) and a visual stimulus naturally associated with that odour (picture of orange) on the movements of the eyes over a complex scene. Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 62 publications
(57 reference statements)
5
65
0
Order By: Relevance
“…This indicates for instance that vision can influence what we hear, touch, and smell, and vice versa. This means that in a multisensory environment, basically each sensory modality is able to affect the observation in another modality (Bresciani et al, 2005;Seigneuric et al, 2010;Shimojo & Shams, 2001;Thesen et al, 2004). As noted before, effects of sensory cues may be multiplied, disambiguated, vetoed, inhibited, or the stimulation may even lead to an emergent or novel effect (de Gelder & Bertelson, 2003;Gottfried & Dolan, 2004;Helbig & Ernst, 2008;Pourtois et al, 2005).…”
Section: External Assessment Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…This indicates for instance that vision can influence what we hear, touch, and smell, and vice versa. This means that in a multisensory environment, basically each sensory modality is able to affect the observation in another modality (Bresciani et al, 2005;Seigneuric et al, 2010;Shimojo & Shams, 2001;Thesen et al, 2004). As noted before, effects of sensory cues may be multiplied, disambiguated, vetoed, inhibited, or the stimulation may even lead to an emergent or novel effect (de Gelder & Bertelson, 2003;Gottfried & Dolan, 2004;Helbig & Ernst, 2008;Pourtois et al, 2005).…”
Section: External Assessment Perspectivementioning
confidence: 99%
“…However, it is evident from gestalt principles that the sensory input from the environment is not simply perceived as the sum of its individual components, but rather as a whole (Lin, 2004). Experiments conducted in laboratory settings show that there is a broad spectrum of non-linear interactions between all sensory modalities (Bresciani et al, 2005;Demattè, Sanabria, Sugarman, & Spence, 2006;Driver & Noesselt, 2008;Seigneuric, Durand, Jiang, Baudouin, & Schaal, 2010;Shimojo & Shams, 2001;Small, 2004;Thesen, Vibell, Calvert, & Österbauer, 2004). This means that when cues from different sensory modalities are integrated, the result is not a simple accumulation of the effects generated by each modality separately.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, Seigneuric, Durand, Jiang, Baudouin, and Schaal (2010), for example, demonstrated that learned associations between a smell (e.g., orange) and a picture of its source (e.g., a picture of an orange) affect visual exploration: In the presence of their corresponding odors, objects are explored more rapidly, and for a shorter time, than other objects in the scene, and this occurs even if participants are not aware of the smells having been presented (see also Demattè, Sanabria, & Spence, 2009;Seo, Roidl, Müller, & Negoias, 2010). As in the case of the crossmodal association between taste and smell, this case can be explained by the regular co-experiencing of two features and, more specifically, of features that normally originate from, and are attributed to, the same environmental object.…”
Section: Lack Of a Straightforward Statistical Explanationmentioning
confidence: 99%
“…wide-field or uniform light conditions) similarly impacts active tracking of an attractive and aversive odorant; and third, an aversive odorant elicits the type of optomotor enhancement seen in the presence of an attractive odorant. Previous work in humans has revealed a cooperative relationship between visual and olfactory stimuli whereby input from one modality serves to modulate the other (Gottfried and Dolan, 2003;Seigneuric et al, 2010;Seo et al, 2010;Zhou et al, 2010). Additionally, although recent work has suggested possible sites of visual-olfactory integration in humans (Zatorre and Jones-Gotman, 1991;Savic et al, 2000), the underlying mechanisms of integration remain unknown.…”
Section: Flies Use the Same Sensorimotor Transformations To Dynamicalmentioning
confidence: 90%